Estudios sobre población urbana en el siglo XX : nacer y morir en Rosario, 1900-1925 - Viglione Arrastia, Hebe M. L. (2010)
Fil: Viglione Arrastia, Hebe M. L. Universidad Nacional de Rosario; Argentina